Diagnosis of Transmissible Venereal Tumors in Bitches - Platelet Indices Are a Remarkable Marker? - Kose, Serkan İrfan and Köse, Ayşe Merve and Koldaş Ürer, Ece and Bahan, Onur and Gözer, Ahmet and Ambarcıoğlu, Pınar (Acta Scientiae Veterinariae, 2023)
Background: Hematological analyses are seen as more preferred laboratory analyses in canine transmissible venereal tumor studies. There is no information about the availability of platelets and their indices in routine practice in canine transmissible venereal tumor cases. Taking this as a starting point, this study analyzed the usefulness of platelet indices in dogs with transmissible venereal tumor in clinical laboratory diagnosis as well as examined the relationship between white blood cells, red blood cells, platelets (PLT), main platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT), and the ratio of main platelet volume to platelets (MPV/PLT). Materials, Methods & Results: In the study, a total of 42 bitches of various breeds were used. Nineteen healthy bitches were used as a control group, and the others 23 with cTVT as a study group. Metastasis was not observed in any of the bitches involved in the study. History, clinical findings, and cytological examinations were evaluated for the diagnosis of cTVT. In animals with hemorrhagic discharge and neoplastic lesions, a vaginal cytological examination was performed. Typical TVT cells with large nuclei and intracytoplasmic vacuoles were observed in the vaginal cytological examinations, and the diagnosis of TVT was made. Healthy bitches (19) and those with TVT (23) were 39.16 5.37 months and 47.61 5.14 months old, respectively. From all animals, 2 mL blood samples were collected from V. cephalica to evaluate PIs in the complete blood count (CBC). Collected blood samples were analyzed using an automated hematology analyzer. As a result of the analysis, WBC, RBC, HGB, HCT, MCV, MCHC, RDW, PLT, MPV, PDW, PCT, and MPV/PLT data were obtained. Mild leukocytosis, an increase in PLT, and a decrease in MCV and MPV/PLT were determined in the study group compared to the control group. Cut-off values in CBC of bitches with TVT were determined as WBC: 13.35 (sensitivity: 78%; specificity: 90%); MCV: 67 (sensitivity: 57%; specificity: 95%); PLT: 315.50 (sensitivity: 65%; specificity: 74%); and MPV/PLT: 0.028 (sensitivity: 78%; specificity: 58%). In CBC analyses, a strong negative correlation between PLT and MPV/PLT was detected in both groups. Discussion: Canine transmissible venereal tumors are common in both stray and pet dogs. It is naturally transferred from animal to animal during mating by live tumor cells. This tumor can commonly affect the external genitalia and internal organs in some cases. It generally has the look of cauliflower, and its surface is ulcerated, inflammatory, hemorrhagic, and infectious. More preferred laboratory analyses are complete blood count and blood chemistry analysis in cTVT for to evaluate the success of treatments. Platelet indices have been investigated in many diseases such as endotoxemia, chronic enteropathy, mammary tumor, parvoviral enteritis, septic peritonitis, lymphoma, pyometra, visceral leishmaniasis, and babesiosis in dogs. There is no information available for either diagnostic or prognostic use of the PIs in canine TVT cases. Ultimately, in light of the presented study’s results, platelet indices, especially PLT and the MPV/PLT ratio, seem to be notable laboratory markers in terms of easy accessibility and low-cost assessment techniques in canine transmissible venereal tumor cases. New data, however, should be established by a thorough follow-up study using a larger sample size and addressing its usefulness as a diagnostic or prognostic marker in canine transmissible venereal tumors. Keywords: platelet indices, complete blood count, transmissible venereal tumor, female dog.